PELATIHAN PENGELOLAAN PENGELUARAN PRODUKTIF TERHADAP LABA AKUNTANSI PADA UMKM - Novy Karmelita Indrawati; Defia Nurbatin; Pudji Lestari (Jurnal Edukasi Pengabdian Masyarakat, 2023)
MSMEs, as small-scale household businesses, often do not have an adequate level of financial management knowledge. The business profit generated, of which the largest portion is usually used to meet family consumption needs, is neglected in favor of business development. with the method of introducing productive finance to their business profits and continuing with management assistance so that MSMEs can make decisions to allocate some of their business profits to productive financial expenditures. Productive expenditure itself can be in the form of business development, investment, or the purchase of productive assets, which can provide additional benefits beyond the business profits that have been realized by MSMEs so far. The program for the importance of productive financial management for MSMEs says that the operating profit generated can support business finances. Implementation of programs and strategies is carried out by providing socialization on productive expenditure to MSMEs actors and providing assistance in choosing productive expenditure according to the resources they have. Financial management assistance allows for consistent monitoring and control of expenditures, particularly productive expenditures. Assistance is expected to improve financial management knowledge of accounting profit and assist SME businesses in making strategic decisions on productive expenditure. Keywords: MSMEs, Financial management, productive expenditure, business development